2000
DOI: 10.1080/003655900750016922
|View full text |Cite
|
Sign up to set email alerts
|

Xanthomonas maltophilia Infection in Chronic Peritoneal Dialysis Patients

Abstract: Xanthomonas maltophilia infection has only been occasionally reported in patients receiving chronic peritoneal dialysis. We describe four cases of Xanthomonas maltophilia infection associated with chronic peritoneal dialysis. Two patients presented with peritonitis and two with exit site infection. All patients were diabetics, who immediately prior to the study had not received antibiotic therapy. Failure to respond to multiple antibiotic therapy resulted in catheter removal in both patients with peritonitis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Baek et al (5) , reported a total of 5 cases including 2 patients with ESI and 3 patients with peritonitis, and 2 patients had catheter loss. Azak A et al (11) , reported a single case, Beatriz Millan Diaz et al (12) , reported single case, and N.Al-Hilali et al (13) reported 4 cases.…”
Section: Discussionmentioning
confidence: 99%
“…Baek et al (5) , reported a total of 5 cases including 2 patients with ESI and 3 patients with peritonitis, and 2 patients had catheter loss. Azak A et al (11) , reported a single case, Beatriz Millan Diaz et al (12) , reported single case, and N.Al-Hilali et al (13) reported 4 cases.…”
Section: Discussionmentioning
confidence: 99%
“…S. maltophilia may cause peritonitis in patients receiving chronic peritoneal dialysis; catheter removal is usually required for cure. 35,36 ANTIMICROBIAL SUSCEPTIBILITY Most isolates of S. maltophilia are resistant to multiple antimicrobial agents. High-level resistance to multiple b-lactam antibiotics is due to two inducible b-lactamases, a zinc-containing penicillinase 37 and a cephalosporinase.…”
Section: Bacteremiamentioning
confidence: 99%
“…22 Stenotrophomonas maltophilia cellulitis can occur at the site of endovascular, peritoneal, jejunostomy, and suprapubic catheters. 50,85,86 Severe cellulitis and myositis without previous trauma have been described in neutropenic and other hospitalized patients. 25,87 The most remarkable type of soft tissue infection due to S. maltophilia is the metastatic involvement in immunosuppressed bacteremic patients as already described, manifesting as multiple nodular lesions surrounded by violaceous erythema, or as ecthyma gangrenosum.…”
Section: Bacteremiamentioning
confidence: 99%
“…103 Abdominal Infection S. maltophilia abdominal infections include cholangitis in patients with biliary tract obstruction due to hepatobiliary malignancies, 104 and peritonitis in patients undergoing chronic peritoneal dialysis. 85,[105][106][107][108] Peritoneal infections respond well to antibiotic treatment, although removal of the intraperitoneal catheter has been advocated in a large number of patients. 52 One case of an infected pancreatic pseudocyst secondary to severe pancreatitis has also been reported.…”
Section: Bacteremiamentioning
confidence: 99%